1987
DOI: 10.1136/ard.46.5.408
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the five histones and poly(adenosine diphosphate-ribose) in drug induced lupus: implications for pathogenesis.

Abstract: SUMMARY Certain drugs are a frequent source of antinuclear antibody (ANA) induction, and ANA is invariably present in the few patients who progress to the drug induced lupus syndrome. This report concerns the fine specificity of the ANA response to hydralazine, penicillamine, and sulphasalazine therapy. Using highly purified individual histones in fluorimetric assays, antihistone antibodies are always detectable, often in large amounts, but the pattern of response to individual histones is variable and not dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…ANAs may be detected in as many as 50–90% of patients depending on the drug, dose and duration of treatment 9. The development of ANAs suggests a drug induced autoimmune phenomenon, resulting in other antibodies than the classic antihistones.…”
Section: Discussionmentioning
confidence: 99%
“…ANAs may be detected in as many as 50–90% of patients depending on the drug, dose and duration of treatment 9. The development of ANAs suggests a drug induced autoimmune phenomenon, resulting in other antibodies than the classic antihistones.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from patients with hydralazine-induced lupus were reported to predominantly react with H3 and H4 (9), although other studies failed to detect a distinct pattern of IgG reactivity with individual histones using solid-phase assays (37) or Western blot (12). Chlorpromazine-induced antihistone antibodies were reported to display relatively uniform binding with the substrates tested (5).…”
Section: Discussionmentioning
confidence: 99%
“…Development ofsolid phase assays was initially difficult owing to problems of immobilisation of cationic histone antigens.' A fluorimetric assay was used by Hobbs et al to detect antibodies to histones using purified histones,53 54 and found to be more sensitive than the acid elution/ reconstitution method. Non-specific antibody binding is reduced by histone saturation of the tyrosine-glutamic acid copolymer coating the cuvettes.…”
mentioning
confidence: 99%